The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1471-0307.12910
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, angiotensin‐converting enzyme inhibitory and anti‐inflammatory activities of fermented camel milk and characterisation of novel bioactive peptides from lactic‐fermented camel milk with molecular interaction study

Abstract: This study was to separate and purify antidiabetic and angiotensin-converting enzyme (ACE) inhibitory peptides from Lactiplantibacillus plantarum KGL3A fermented camel milk. After 48 h of fermentation at 37°C, ɑ-amylase inhibition, ɑ-glucosidase inhibition, lipase inhibition and ACE inhibitory activities were 80.94%, 64.45%, 63.93%, and 77.53%, respectively in fermented camel milk. Optimisation of growth condition for the evaluation of maximum peptide production was evaluated by measuring proteolytic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…An increasing number of studies have shown that the inhibitory effect of competitive inhibitors on ACE is strong. 6,8,40 In the current study, the T -score and C -score for the optimal docking mode between ACE and EASPKPV were 8.42 and 5.0, respectively, both higher than the accepted threshold. 25 In addition, the hydrogen bond distance between EASPKPV and the five central active sites (Gln281, Ala354, Glu376, Lys511, and Tyr523) was short (2.69–3.05 Å), suggesting that EASPKPV had a strong affinity towards ACE.…”
Section: Resultsmentioning
confidence: 49%
“…An increasing number of studies have shown that the inhibitory effect of competitive inhibitors on ACE is strong. 6,8,40 In the current study, the T -score and C -score for the optimal docking mode between ACE and EASPKPV were 8.42 and 5.0, respectively, both higher than the accepted threshold. 25 In addition, the hydrogen bond distance between EASPKPV and the five central active sites (Gln281, Ala354, Glu376, Lys511, and Tyr523) was short (2.69–3.05 Å), suggesting that EASPKPV had a strong affinity towards ACE.…”
Section: Resultsmentioning
confidence: 49%
“…Bioconversion is mainly made up of fermentation using probiotics, so it is possible to enhance the nutritional and physiological values through enzymatic conversion of raw materials of food. Especially, in the case of Lactiplantibacillus plantarum used in this study, bioactivity such as antioxidant, antiinflammation, and anti-diabetes was reported, and recent studies have reported cancer cell death through MAPK signaling pathways and suppression of metastasis through MMP-1/3 inhibition (Zommara et al, 2022;Shukla et al, 2022). Therefore, research on improving physiological activity and enhancing nutritional value of food products through bioconversion using Lactiplantibacillus plantarum in natural products continues.…”
Section: Introductionmentioning
confidence: 70%
“…Previously, the nutritional and health benefits of fermentation have not been widely recognized beyond its use in food processing as a means of diversification and preservation; however, fermentation can enhance nutrient bioavailability, 3,17 reduce antinutritional factors (ANFs) content, 2,28,29 increase levels of bioactive peptides (BAPs), 4,[30][31][32] improve sensory properties, 23,33 and detoxify and reduce mycotoxins in food. 17,34 For example, ⊍-glucosidase, which hydrolyses legume oligosaccharides, including verbascose, stachyose and raffinose, into digestible sugars is activated during fermentation 35 to minimize the discomfort they cause in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the nutritional and health benefits of fermentation have not been widely recognized beyond its use in food processing as a means of diversification and preservation; however, fermentation can enhance nutrient bioavailability, 3,17 reduce antinutritional factors (ANFs) content, 2,28,29 increase levels of bioactive peptides (BAPs), 4,30‐32 improve sensory properties, 23,33 and detoxify and reduce mycotoxins in food 17,34 …”
Section: Introductionmentioning
confidence: 99%